CULTURAL CONTINUITY AND CHANGE: MODERNIZATION AMONG THE RONGMEI TRIBE - Gonmei, Ngampingampou; Gangmei, Makhou (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This ethnographic research offers a thorough examination of the metamorphosis undergone by the Rongmei people in Northeast India as they shift from tradition to modernization. It examines the complex dynamics of how modernization has transformed the traditional Rongmei lifestyle. This research, using a detailed anthropological approach, elucidates the intricate relationship between tradition and modernization in Rongmei society, providing significant insights on cultural preservation and socio-economic change in indigenous groups. This research provides an in-depth analysis of the intricate alterations inside Rongmei society during modernization and religious change.